2015
DOI: 10.1108/jfmm-09-2012-0055
|View full text |Cite
|
Sign up to set email alerts
|

Fashion orientation, shopping mall environment, and patronage intentions

Abstract: Purpose – The purpose of this paper is to explore female fashion shoppers’ perception and response to the mall environment. Specific objectives include a conceptual model of female fashion shoppers’ experience in a mall environment incorporating fashion orientation, store personality, shopping mall perception, shopping value, and patronage intentions. Design/methodology/approach – Empirical testing is done with a latent path structural e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 55 publications
5
27
2
2
Order By: Relevance
“…This research found that CPV had no effect on Patronage Intention, not supporting the previous studies of Rahman et al (2016); Michon et al (2015); Jamal and Sharifuddin (2014). CPV is consumers' whole assessment about the usefulness of products or services based on their perceptions of the product benefits they will receive (Zeithaml, 1988).…”
Section: Customer Perceived Value (Cpv)contrasting
confidence: 78%
“…This research found that CPV had no effect on Patronage Intention, not supporting the previous studies of Rahman et al (2016); Michon et al (2015); Jamal and Sharifuddin (2014). CPV is consumers' whole assessment about the usefulness of products or services based on their perceptions of the product benefits they will receive (Zeithaml, 1988).…”
Section: Customer Perceived Value (Cpv)contrasting
confidence: 78%
“…al (2017) that utilitarian shopping value play a significant role in consumer behavioral intention. This substantiates earlier works by Michon et. al (2015) and Bakirtas et.…”
Section: Discussionsupporting
confidence: 94%
“…al (2015) with the expension of knowledge about youth market segment. Previously, Michon et. al (2015) and Bakirtas et.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations